Analisis Tingkat Konsumsi Ikan Pada Keluarga Pelaksana Program Buruan Sae Kota Bandung - Irfy, Mochamad Zidane Fahrul; Suryana, Asep Agus Handaka; Rochima, Emma; Maulina, Ine (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to analyze the level of fish consumption, fish needs, and factors that influence the level of family fish consumption in families implementing the Buruan Sae Program in Bandung City. This research was carried out in three groups of the Buruan Sae Program. The implementation will be carried out in October 2023 – March 2024. The research method used is the case study method (case study). The respondents in this research were 46 people who were program implementers from three groups of the Buruan Sae Program. This research applies a saturated sampling or census method. Analysis of fish consumption levels and fish needs using quantitative analysis and analysis of factors that influence fish consumption levels using multiple linear regression analysis. The results show that the third group's annual per capita fish consumption is 17.68 kg/capita/year. Annual per capita fish consumption among these groups is lower than the average for Bandung City and West Java Province. Analysis of fish needs shows that the Warnasari Mandiri Group is experiencing a surplus, while Jasmine Integrated Farm and Belpas 15 are experiencing a deficit. Factors that influence the level of fish consumption include education and number of family members, age, income and experience do not have a significant influence.